PHYSICAL ACTIVITY AND THE QUALITY OF LIFE OF STUDENTS AT CONSTANTINE THE PHILOSOPHER UNIVERSITY IN NITRA (Fiep Bulletin - online, 2014)
The aim of the work is the evaluation of the quality of life in the relationship to level of physical activity of students CPU in Nitra. The research file was made of 424 students with specializations of Teacher training study programmes. The collection of the data was provided by questionnaire method. The relationship between the level of sport activity and the areas of life quality was evaluated by using correlation analysis. The results show differentiated relationship between the level of sport activity and importance, which the students attribute to different areas of life quality. By students with low (2.61 ± 1.07 per week) and high frequency (5.52 ± 0.63 per week) of physical activity were not noticed important relationships with satisfaction in particular areas of life quality. The satisfaction with life quality was found out by the students with average physical activity (3.76 ± 1.05 per week) in areas of physical (p
Keywords: physical activity; well-being; correlation; students; university